2000
DOI: 10.1093/ajcn/72.4.976
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and thyroid hormone status in selenium-deficient phenylketonuric and hyperphenylalaninemic patients

Abstract: Supplementation with selenium seems to be advisable for patients consuming diets low in natural protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 21 publications
5
48
1
6
Order By: Relevance
“…One of them is glutathione metabolism, which is influenced by the presence of free radicals. Van Bakel et al (2000) showed in PKU and HPA patients that selenium in their plasma correlated well with their erythrocyte glutathione peroxidase and the antioxidant status was low in both groups of patients. Also, the authors reported that their a-tocopherol, albumin and uric acid levels were not different as compared with controls and recommended selenium supplementation in their diet.…”
Section: Discussionmentioning
confidence: 95%
“…One of them is glutathione metabolism, which is influenced by the presence of free radicals. Van Bakel et al (2000) showed in PKU and HPA patients that selenium in their plasma correlated well with their erythrocyte glutathione peroxidase and the antioxidant status was low in both groups of patients. Also, the authors reported that their a-tocopherol, albumin and uric acid levels were not different as compared with controls and recommended selenium supplementation in their diet.…”
Section: Discussionmentioning
confidence: 95%
“…The natural protein restricted diet of PKU patients may result in some essential nutrient deficiencies; ie selenium (Van Bakel et al, 2000) or cobalamin (Hanley et al, 1996). To prevent these deficiencies, supplementation with several of these micronutrients has been added to the special formulas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the normal glutathione values observed in our PKU patients would further support the beneficial effects of low tHcy and cysteine concentrations. However, this hypothesis should be considered with caution because other factors present in PKU patients may increase oxidative stress, such as selenium deficiency in patients with poor dietary adherence (Van Bakel et al, 2000), or the decreased ubiquinone-10 values observed in serum (Artuch et al, 1999) and cells (Colomé et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Phe-restricted diet is a considerable risk factor for nutritional deficiencies and requires close supervision to prevent these. Patients may be at risk of mineral and trace element deficiencies such as zinc (Zn), selenium (Se) or iron (Fe) [2,3]. Clinical consequences include anaemia and growth retardation [4].…”
Section: Introductionmentioning
confidence: 99%